Corrosion-resistant alloy material, preparation method of corrosion-resistant alloy material, protective coating for welding seam of offshore wind turbine generator and preparation method of protective coating

By using corrosion-resistant alloy materials and laser cladding or thermal spraying technology to prepare protective coatings in the weld area of ​​offshore wind power tower, the serious problem of weld corrosion is solved, the corrosion resistance and mechanical properties are improved, and the weld is realized. Effective protection and cost reduction.

CN119194167APending Publication Date: 2024-12-27NORTH CHINA ELECTRICAL POWER RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411119930.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Due to welding defects and severe marine corrosion environment in the offshore wind power tower weld area, the protection effect of anti-corrosion paint is poor, resulting in serious corrosion, affecting the long-term safety and stable operation of the unit, and the anti-corrosion repair of the weld is difficult and costly.

Method used

Corrosion-resistant alloy materials (Cu: 35-50%, Mo: 1-5%, Si: 0.8-1.5%, Al: 1-2%, Sb: 1-2%, and the balance is Ni) and laser cladding are used. Technology or thermal spraying technology prepares protective coatings on the surface of the weld to improve the corrosion resistance and mechanical properties of the weld.

Benefits of technology

It significantly improves the corrosion resistance and mechanical properties of the weld area, extends the life of offshore wind power towers, reduces corrosion protection costs, and ensures the safe and reliable operation of the unit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194167A_ABST
    Figure CN119194167A_ABST
Patent Text Reader

Abstract

The invention provides a corrosion-resistant alloy material and a preparation method thereof as well as a protective coating for a welding seam of an offshore wind turbine generator and a preparation method of the protective coating. The corrosion-resistant alloy material comprises, by mass, 35%-50% of Cu, 1%-5% of Mo, 0.8%-1.5% of Si, 1%-2% of Al, 1%-2% of Sb and the balance Ni. The protective coating aiming at the weld joint of the offshore wind turbine generator set, provided by the invention, has corrosion resistance and good mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of metal corrosion protection, and specifically relates to a corrosion-resistant alloy material and a preparation method thereof, and a protective coating for welds of offshore wind turbines and a preparation method thereof. Background Art

[0002] The tower of an offshore wind turbine is the supporting structure of the entire unit. The safety and reliability of the tower are crucial for ensuring the long-term, stable service of the offshore wind turbine. A single tower is typically constructed from 33-50 welded sections. The truss beneath the tower is constructed from 3-5 large sections, connected by high-strength bolts. Butt welds are used to connect the flange to the tower and the short pipe sections within the large sections. A typical offshore wind turbine tower may contain thousands of welds of various types. As the connection between the various load-bearing components of the tower, the quality and reliability of these welds are crucial to the long-term, safe, and stable operation of offshore wind power.

[0003] Because the welding process involves rapid localized heating and cooling, even with carefully controlled welding parameters, the weld area after formation can still contain numerous defects, such as weld porosity and uneven slag composition. In a corrosive marine environment, weld areas with these defects are highly susceptible to corrosion. Localized weld defects can lead to serious localized corrosion, such as pitting and stress corrosion cracking, posing a significant threat to the safe and stable operation of offshore wind turbines. Current corrosion protection measures for metal structural components of offshore wind turbine towers include applying anti-corrosion paint and supplementing with impressed current protection. Anti-corrosion paint can protect most metal components from contact with the marine corrosive environment, slowing their corrosion. However, anti-corrosion paint is less effective for welds. This is because weld defects within the weld prevent the paint from fully penetrating during application, resulting in missed coatings and pinholes. Furthermore, defects such as weld slag and spatter can cause uneven paint film thickness in the area where they occur, impairing paint adhesion. Because the anti-corrosion coating and the substrate are mechanically, polarly, and chemically attached, the bonding strength between the anti-corrosion coating and the substrate is poor, making it prone to peeling and losing its protective effect. Furthermore, welds in the splash zone are subject to more severe corrosion. The surfaces of metal components in the splash zone are exposed to a corrosive environment characterized by alternating wet and dry conditions and high salt and oxygen content. This allows corrosive media to easily enter the paint, causing corrosion of the inner metal layer, resulting in wrinkling, bubbling, and flaking of the paint film. Furthermore, the surfaces of metal components in the splash zone are also subjected to the scouring effects of seawater and the sediment in it, further accelerating the flaking of the anti-corrosion paint and corroding the metal substrate.

[0004] Because the anti-corrosion paint in the weld area is not firmly bonded to the metal substrate, and the harsh marine corrosion environment will further degrade the protective effect of the anti-corrosion paint, the weld areas of offshore wind turbine structural components often suffer from severe corrosion damage, posing a potential hazard to the long-term safe and stable operation of offshore wind turbines. Therefore, it is necessary to implement special anti-corrosion measures for the weld areas of offshore wind turbine structural components. The current anti-corrosion measure for the weld areas of offshore wind turbine towers and towers is to regularly repair the anti-corrosion paint. However, after the anti-corrosion repair, the bonding strength of the anti-corrosion paint in the weld area is still poor and cannot protect the metal substrate from corrosion for a long time. In addition, it is difficult to carry out anti-corrosion repair of the welds of towers located below sea level, and the technical cost is high.

[0005] Therefore, developing a corrosion protection technology for welds of offshore wind turbine towers and other structural parts is of great significance for saving anti-corrosion costs and ensuring the long-term safe operation of offshore wind turbines. Summary of the Invention

[0006] To address the aforementioned problems in the prior art, the present invention provides a corrosion-resistant alloy material and a method for preparing the same, as well as a protective coating for the welds of offshore wind turbines and a method for preparing the same. The protective coating for the welds of offshore wind turbines provided by the present invention provides both corrosion resistance and good mechanical properties.

[0007] In order to achieve the above-mentioned purpose, according to the first aspect of the present invention, a corrosion-resistant alloy material is provided, which comprises the following components by mass: Cu: 35-50%, Mo: 1-5%, Si: 0.8-1.5%, Al: 1-2%, Sb: 1-2%, and the remainder is Ni.

[0008] Copper and iron have very low solid solubility. The presence of copper in the corrosion-resistant alloy can reduce the dilution rate of the coating, preventing the diffusion of large amounts of iron into the coating, which can lead to excessive iron content and affect corrosion resistance. Therefore, the copper content in the corrosion-resistant alloy is 35-50 wt.%. Nickel in the corrosion-resistant alloy can improve both the corrosion resistance and the mechanical properties of the material.

[0009] Copper-nickel alloy is a single-phase solid solution within the entire composition range. In the seawater corrosion environment, copper elements react with the electrolyte ions in seawater to form a denser Cu2O film, which can protect the material from contact with seawater and continue the corrosion process. However, due to the presence of a large number of vacancy defects in the Cu2O generated during the corrosion process, the protective ability of Cu2O is greatly weakened. Ni atoms in copper-nickel alloys can be doped into the ion holes in the Cu2O semiconductor film during the corrosion process, thereby improving the stability of the Cu2O semiconductor film. More Ni atoms can also improve the mechanical properties of the material, and resist the damage to the coating caused by seawater erosion and sediment impact. However, in Cl- Under the action of corrosive ions such as copper, nickel alloys will undergo severe local corrosion, which is manifested as intergranular corrosion and pitting corrosion. Therefore, other elements are needed to improve the corrosion resistance of copper-nickel alloys.

[0010] Molybdenum can be used to improve the material's resistance to intergranular corrosion. A small amount of molybdenum can segregate at the grain boundaries. The intergranular molybdenum content is higher than that within the grains, which can prevent intergranular corrosion.

[0011] Al combines with Ni to form Ni3Al, producing a significant precipitation hardening effect, improving the coating's mechanical properties and resistance to seawater erosion. Furthermore, Al forms a dense Al2O3 film during the corrosion process, enhancing the stability of the Cu2O film and increasing the charge transfer resistance of the oxide film, further improving the material's resistance to localized corrosion. However, excessive aluminum can cause cracking in the coating and make preparation difficult, so a small amount of Al is added.

[0012] Silicon has a deoxidizing effect, and a small amount of silicon can significantly improve the mechanical properties of the alloy, but too much silicon will cause the coating to crack during cladding, and the appearance of cracks is not conducive to improving the corrosion resistance of the material.

[0013] Antimony can reduce the eutectic formed by Cu and Cu2O at the grain boundaries, improve the corrosion resistance of copper, and reduce its electrical conductivity and thermal conductivity. Antimony can react with cuprous oxide in oxygen-containing copper to form spherical particles with high melting points, which are distributed in the grains. This can eliminate the eutectic that may be formed between copper and cuprous oxide on the grain boundaries and improve the plasticity of copper.

[0014] In some preferred embodiments of the present invention, the corrosion-resistant alloy material is in powder form with a particle size of 200 to 400 meshes.

[0015] In some preferred embodiments of the present invention, the corrosion-resistant alloy material includes the following components by mass: Cu: 45-50%, Mo: 1-3%, Si: 0.8-1.0%, Al: 1-1.5%, Sb: 1-1.5%, and the balance is Ni.

[0016] In some preferred embodiments of the present invention, the corrosion-resistant alloy material comprises the following components by mass: Cu: 48%, Mo: 2%, Si: 1.0%, Al: 1%, Sb: 1%, and the balance is Ni.

[0017] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned corrosion-resistant alloy material, which comprises:

[0018] Step S1, weighing raw materials of Cu, Mo, Si, Al, Sb, and Ni, placing them in a smelting container, evacuating to 1-100 Pa, then filling with a protective atmosphere to 105-110 kPa, and heating to 1300-1500° C. to obtain a molten alloy;

[0019] Step S2: injecting the alloy liquid into an atomizing device for atomization and powdering treatment; the atomization temperature is 1160-1250° C.; and the atomization pressure is 3-4 MPa.

[0020] In some preferred embodiments of the present invention, the atomization powdering process is carried out under a protective atmosphere. The protective atmosphere can be selected from nitrogen and argon. In some preferred embodiments of the present invention, the crucible in the smelting container is a water-cooled copper crucible with a crucible capacity of 20 kg, a maximum smelting temperature of 2200°C, a maximum smelting power of 250 kW, and a vacuum limit of 3.0×10 -4 Pa.

[0021] In some preferred embodiments of the present invention, after the alloy liquid is obtained, it is kept warm for 10 minutes to better mix the various metal components.

[0022] In some preferred embodiments of the present invention, step S2 includes:

[0023] The alloy liquid is introduced into an atomizing device equipped with a nozzle, through which a protective gas is introduced for atomization and powdering. The protective gas has a flow rate of 15 to 25 m / s and a pressure of 3.5 to 4.5 MPa upon reaching the nozzle. The flow rate of the alloy liquid in the atomizing device is 0.2 to 0.8 kg / min. In the nozzle, the protective gas acts on the alloy liquid column, dispersing, crushing, and cooling the alloy liquid column to obtain alloy powder.

[0024] In some preferred embodiments of the present invention, after step S2, the preparation method further comprises: step S3, sieving the powder obtained by the atomization pulverization process. Preferably, the powder is sieved to obtain a 200-400 mesh powder. Preferably, the sieving is performed using a vibrating screen. Preferably, after sieving, the obtained powder is quickly vacuum-packaged to prevent oxidation.

[0025] According to another aspect of the present invention, a protective coating for welds of offshore wind turbines, which is prepared from the above-mentioned corrosion-resistant alloy material, is provided.

[0026] In some preferred embodiments of the present invention, the protective coating for the weld of an offshore wind turbine has a thickness of 400 to 700 microns and a surface Fe content of less than 5 wt %. The surface refers to the area within 50 microns inward from the outer surface of the protective coating for the weld of an offshore wind turbine.

[0027] According to another aspect of the present invention, a method for preparing the protective coating for the welds of offshore wind turbines is provided, comprising: using laser cladding technology to prepare the protective coating for the welds of offshore wind turbines on the surface of the welds, wherein the laser power is 1000-2000W, the beam diameter is 1-2.5mm, and the powder feeding method is circular synchronous powder feeding. The laser cladding technology is preferably applied in a tower manufacturing workshop, after the tower welding process is completed, using the laser cladding technology to prepare the protective coating for the welds of offshore wind turbines on the surface of the welds.

[0028] Preferably, the weld is pretreated before laser cladding; preferably, the pretreatment includes: using an angle grinder to grind the surface of the weld flat, removing welding slag and impurities on the surface, and using acetone or anhydrous ethanol to clean the weld and its surroundings.

[0029] Preferably, after laser cladding is completed, the protective coating for the welds of offshore wind turbines is polished with an angle grinder to remove unmelted powder particles and cladding marks on the surface, ensuring a smooth surface without protrusions, and an anti-corrosion paint is applied to the tower surface. Preferably, the anti-corrosion paint is an epoxy zinc-rich primer, epoxy glass flake paint, and a polysiloxane topcoat. This preference helps prevent galvanic corrosion caused by contact between the protective coating for the welds of offshore wind turbines prepared on the weld surface and the substrate and seawater.

[0030] Preferably, the laser power is 1500-2000W, the laser head moving speed is 5-15cm / s, the step during the cladding process is 0.4-0.8mm, the powder feeding amount is 1-4kg / h, the powder feeding gas flow rate is 5-15L / min, and the protective gas flow rate is 15-20L / min.

[0031] In some preferred embodiments of the present invention, the method for preparing the protective coating for the weld of an offshore wind turbine generator set on the weld surface using laser cladding technology includes:

[0032] Step A1, fixing the laser cladding head on the robotic arm;

[0033] Step A2: Setting the trajectory of the laser cladding head during the cladding process to ensure that the cladding area covers the weld and the surrounding area. The scanning direction of the laser cladding head is the longitudinal direction of the tower, and the stepping direction is the tangential direction of the tower. During the cladding process, the laser head's trajectory is controlled by axis linkage. To accurately control the distance between the cladding head and the area to be clad and ensure cladding quality, an eddy current rangefinder is used to assist in controlling the movement of the cladding in the z-axis direction.

[0034] The power of the laser is preferably 1500W, the moving speed of the laser head is preferably 10cm / s, the stepping distance during the cladding process is preferably 0.6mm, the powder feeding amount is preferably 2kg / h, the powder feeding gas flow rate is preferably 5L / min, and the flow rate of the shielding gas is preferably 15L / min;

[0035] Step A3: Use an angle grinder to grind the prepared protective coating for the weld of the offshore wind turbine to remove unmelted powder particles and cladding marks on the surface, ensure a smooth surface without protrusions, and ensure the bonding strength between the anti-corrosion paint and the protective coating for the weld of the offshore wind turbine.

[0036] According to another aspect of the present invention, a method for preparing the protective coating for the welds of offshore wind turbines is provided, comprising: applying the protective coating for the welds of offshore wind turbines to the weld surface using thermal spraying technology, wherein the powder feed rate is controlled to be 60-80 g / min and the spraying distance is 300-400 mm. A preferred application of the thermal spraying technology is to apply the protective coating for the welds of installed towers and towers in service to the weld surface when corrosion occurs. In some preferred embodiments of the present invention, the welds and surrounding surfaces are sprayed using a handheld flame spraying device, wherein the kerosene flow rate is 4.5-6.5 GPH, preferably 5 GPH; the oxygen flow rate is 1800-2000 SCFH, preferably 1800 SCFH; and the powder feed rate is preferably 60 g / min.

[0037] Preferably, after the thermal spraying is completed, the surface of the protective coating on the weld of the offshore wind turbine is ground clean using an angle grinder, and anti-corrosion paint is applied around the weld.

[0038] The protective coating for the welds of offshore wind turbines provided by the present invention is suitable for corrosion protection of weld areas of offshore wind turbine towers, tower frames and other structural parts.

[0039] The corrosion-resistant alloy material provided by the present invention can be used for corrosion protection of welds of offshore wind turbine towers, tower frames and other structural parts before they leave the factory, and can also be used for corrosion protection of welds of towers and tower frames in existing offshore wind farms. For structural parts before leaving the factory, it is recommended to use laser cladding technology to prepare a protective coating with metallurgical bonding for the welds of offshore wind turbines; and for on-site corrosion protection of offshore wind turbines, considering the difficulty of construction, it is recommended to use thermal spraying technology. Although the protective coating for the welds of offshore wind turbines prepared by thermal spraying technology is mechanically bonded to the substrate, its corrosion resistance life is lower than that of the protective coating for the welds of offshore wind turbines obtained by laser cladding, but thermal spraying technology has the advantages of high spraying efficiency, less environmental impact on coating quality, and more convenient on-site construction.

[0040] The corrosion protection solution provided by the present invention can significantly improve the corrosion resistance of the weld areas of offshore wind turbine towers and other structural parts in different marine corrosion environments, extend the service life of offshore wind turbine towers, tower frames and other structural parts, and greatly improve the safety and reliability of offshore wind turbines during service. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 A schematic diagram of the protective coating for the welds of an offshore wind turbine generator system prepared in Example 1 is shown.

[0042] Figure 2 A scanning electron microscope image of a cross section of the protective coating for the weld of an offshore wind turbine in Example 1 and an element distribution curve of a cross section of the protective coating for the weld of an offshore wind turbine in Example 1 are shown.

[0043] Figure 3 The microscopic morphology of the protective coating on the weld of the offshore wind turbine in Example 1 after corrosion is shown.

[0044] Figure 4 The polarization curves of Q345B steel and the protective coating for the weld of an offshore wind turbine in Example 1 in a 3.5 wt. % sodium chloride solution are shown.

[0045] Figure 5 The figure shows the effect of preparing a protective coating on the weld surface for an offshore wind turbine.

[0046] The accompanying drawings are numerals as follows:

[0047] 1-Protective coating for welds of offshore wind turbines, 2-Weld area, 3-Welding heat affected zone, 4-Matrix, 5-Eutectic Mo-rich area, 6-Primary phase area. DETAILED DESCRIPTION

[0048] In order to have a clearer understanding of the technical features, objectives and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be understood as limiting the scope of implementation of the present invention.

[0049] Example 1

[0050] This embodiment provides a method for preparing a protective coating on the weld surface of an offshore wind turbine, which includes the following steps:

[0051] 1. Preparation of corrosion-resistant alloy materials

[0052] The corrosion-resistant alloy material composition is: Cu: 48 wt.%, Mo: 2 wt.%, Si: 1 wt.%, Al: 1 wt.%, Sb: 1 wt.%, Ni: balance.

[0053] According to the composition of the alloy powder, corresponding masses of copper, nickel, aluminum, molybdenum, silicon and antimony are weighed as raw materials, ensuring that the surface of the raw materials is clean and free of pollution.

[0054] The smelting process is mainly carried out in the smelting chamber. Before smelting, a vacuum pump is used to evacuate the atmosphere in the smelting chamber to a vacuum state, and a nitrogen cylinder is used to provide protective nitrogen for the smelting process. After the raw materials are weighed according to the stated mass fraction, they are placed in a water-cooled copper crucible in a vacuum medium-frequency induction heating furnace. The furnace is then evacuated to 50 Pa and filled with argon to 110 kPa. The smelting power is set to 200 kW and the raw materials in the crucible are heated to 1400 ° C using a resistance wire to obtain a molten alloy. The holding power is then adjusted to 50 kW and the holding time is 10 minutes to ensure that the molten metal is fully mixed.

[0055] After the smelting process is completed, open the gas valve, fill the atomizing chamber with nitrogen, and turn on the water cooling device of the atomizing chamber. Open the atomizing gas valve, and the preheated high-purity, high-pressure nitrogen is accelerated through the Laval structure cavity to form a supersonic airflow. When the gas reaches the atomizing nozzle, the airflow velocity is 20m / s and the pressure is 4MPa. After the airflow velocity and pressure at the nozzle are stable, the molten metal obtained by smelting is slowly poured from the crucible into the tundish with a conduit. At this time, the melt temperature is 1350℃, and the flow rate of the molten metal is controlled to be 0.6kg / min.

[0056] The molten metal in the tundish is introduced into the nozzle and atomized into powder through the nozzle.

[0057] After atomization and pulverization, the powder is vibrated and sieved using 200-mesh and 400-mesh sieves. After the powder is classified, the 200-400-mesh metal powder is quickly vacuum-packed to prevent oxidation, thereby obtaining a corrosion-resistant alloy material.

[0058] 2. Weld surface preparation Protective coating for welds of offshore wind turbines

[0059] Figure 1 A schematic diagram of the protective coating for the welds of offshore wind turbines prepared in this embodiment is shown.

[0060] Use an angle grinder to clean the weld surface and remove welding slag and impurities on the weld surface. Use an angle grinder to grind the weld and the surrounding area to remove impurities and dirt generated during the welding process. Use an angle grinder to grind the weld edge to prevent the height difference between the weld edge and the substrate from being too large, resulting in poor cladding effect. Grind the junction between the weld edge and the substrate smooth, and then wipe the surface of the area to be clad 1 with alcohol or acetone. The cladding area covers the weld area 2, the weld heat-affected zone 3, and part of the substrate 4. Set the movement trajectory of the cladding head during the cladding process to ensure that the cladding area covers the weld and the surrounding area. The movement route of the laser head during the cladding process is controlled by 3-axis linkage. In order to accurately control the distance between the cladding head and the area to be clad and ensure the cladding quality, an eddy current rangefinder is used to assist in controlling the movement of the cladding in the z-axis direction. The laser power during cladding is 1500W, the laser head movement speed is 10cm / s, the step size during the cladding process is 0.6mm, the powder feeding amount is 2kg / h, the powder feeding gas size is 5L / min, and the shielding gas size is 15L / min. The average thickness of the protective coating prepared for the welds of offshore wind turbines is 630μm, and the surface iron content is controlled to less than 5wt.%.

[0061] Example 2

[0062] This embodiment provides a method for preparing a protective coating on the weld surface of an offshore wind turbine, which includes the following steps:

[0063] 1. Selection and preparation of corrosion-resistant alloy materials

[0064] The corrosion-resistant alloy material components used are: Cu: 48 wt.%, Mo: 2 wt.%, Si: 1 wt.%, Al: 1 wt.%, Sb: 1 wt.%, Ni: balance.

[0065] According to the composition of the alloy powder, corresponding masses of copper, nickel, aluminum, molybdenum, silicon and antimony are weighed as raw materials, ensuring that the surface of the raw materials is clean and free of pollution.

[0066] Before smelting, a vacuum pump was used to evacuate the atmosphere in the smelting chamber, and a nitrogen cylinder was used to provide protective nitrogen during the smelting process. The raw materials were weighed according to the specified mass fraction and placed in a water-cooled copper crucible in a vacuum medium-frequency induction heating furnace. The furnace was then evacuated to 50 Pa and filled with argon to 110 kPa. The smelting power was set to 200 kW, and the raw materials in the crucible were heated to 1400°C using a resistance wire to obtain a molten alloy. The holding power was then adjusted to 50 kW and the holding time was 10 minutes to ensure thorough mixing of the molten metal.

[0067] After the smelting process is completed, open the gas valve, fill the atomizing chamber with nitrogen, and turn on the water cooling device of the atomizing chamber. Open the atomizing gas valve, and the preheated high-purity, high-pressure nitrogen is accelerated through the Laval structure cavity to form a supersonic airflow. The gas velocity when it reaches the atomizing nozzle is 20m / s and the pressure is 4MPa. After the air velocity and pressure at the nozzle are stable, the molten metal obtained by smelting is slowly poured from the crucible into the tundish with a conduit. At this time, the melt temperature is 1350℃, and the flow rate of the molten metal is controlled to be 0.6kg / min.

[0068] The molten metal in the tundish is introduced into the nozzle and atomized into powder through the nozzle.

[0069] After atomization and pulverization, the powder is vibrated and sieved using 200-mesh and 400-mesh screens. After the powder is classified, the 200-400-mesh metal powder is quickly vacuum-packaged to prevent oxidation, thereby obtaining the corrosion-resistant alloy material.

[0070] 2. Preparation of tower girth weld surface Pretreatment of protective coating for welds of offshore wind turbines

[0071] After the two tower sections on the welding roller frame are connected and welded, the weld seam is allowed to cool. An angle grinder is then used to grind the weld seam and surrounding area to remove impurities and contaminants generated during the welding process, exposing the metal substrate. The welding roller frame is controlled to rotate the tower, and the laser cladding head is secured to the robotic arm. The arm's position is adjusted to ensure a distance of 10-15 mm from the workpiece surface. The laser head moves in an oscillating forward direction, meaning that during cladding, the laser head moves radially of the tower and in a stepping direction tangentially.

[0072] The trajectory of the laser head during the cladding process is set according to the weld width. The moving length of the laser head is twice the weld width to ensure that the cladding area covers the weld and the heat-affected zone of the weld. In order to accurately control the distance between the cladding head and the area to be clad and ensure the cladding quality, an eddy current rangefinder is used to assist in controlling the movement of the cladding in the z-axis direction. The laser power during cladding is 1500W, the moving speed of the laser head is 10cm / s, the step size during the cladding process is 0.6mm, the powder feeding amount is 2kg / h, the powder feeding gas size is 5L / min, and the shielding gas size is 15L / min. The average thickness of the protective coating prepared for the welds of offshore wind turbines is 652μm, and the surface iron content is controlled to be less than 5wt.%.

[0073] The protective coating on the weld seams of offshore wind turbines is polished using a wire brush and then an angle grinder to remove any cladding marks and maintain a smooth, clean weld surface. After the protective coating cools, the tower is coated with an anti-corrosion paint consisting of an epoxy zinc-rich primer, epoxy glass flake paint, and a polysiloxane topcoat.

[0074] Example 3

[0075] This embodiment provides a method for preparing a protective coating on the weld surface of an offshore wind turbine, which includes the following steps:

[0076] 1. Selection and preparation of corrosion-resistant alloy materials

[0077] The corrosion-resistant alloy material components used are: Cu: 48 wt.%, Mo: 2 wt.%, Si: 1 wt.%, Al: 1 wt.%, Sb: 1 wt.%, Ni: balance.

[0078] Before smelting, a vacuum pump was used to evacuate the atmosphere in the smelting chamber, and a nitrogen cylinder was used to provide protective nitrogen during the smelting process. The raw materials were weighed according to the specified mass fraction and placed in a water-cooled copper crucible in a vacuum medium-frequency induction heating furnace. The furnace was then evacuated to 50 Pa and filled with argon to 110 kPa. The smelting power was set to 200 kW, and the raw materials in the crucible were heated to 1400°C using a resistance wire to obtain a molten alloy. The holding power was then adjusted to 50 kW and the holding time was 10 minutes to ensure thorough mixing of the molten metal.

[0079] After the smelting process is completed, open the gas valve, fill the atomizing chamber with nitrogen, and turn on the water cooling device of the atomizing chamber. Open the atomizing gas valve, and the preheated high-purity, high-pressure nitrogen is accelerated through the Laval structure cavity to form a supersonic airflow. The gas velocity when it reaches the atomizing nozzle is 20m / s and the pressure is 4MPa. After the air velocity and pressure at the nozzle are stable, the molten metal obtained by smelting is slowly poured from the crucible into the tundish with a conduit. At this time, the melt temperature is 1350℃, and the flow rate of the molten metal is controlled to be 0.6kg / min.

[0080] The molten metal in the tundish is introduced into the nozzle and atomized into powder through the nozzle.

[0081] After atomization and pulverization, the powder is vibrated and sieved using 200-mesh and 400-mesh screens. After the powder is classified, the 200-400-mesh metal powder is quickly vacuum-packaged to prevent oxidation, thereby obtaining the corrosion-resistant alloy material.

[0082] 2. Preparation of protective coating on tower fillet weld surface for offshore wind turbines

[0083] After the tower frame fillet welds are completed, the welds and surrounding areas are ground with an angle grinder to remove impurities and contaminants generated during the welding process, exposing the metal matrix. A handheld laser cladding head is then used to apply a protective coating to the fillet welds, specifically for offshore wind turbines.

[0084] The operator uses a handheld laser head to prepare a protective coating for the welds of offshore wind turbines on the welds and surrounding surfaces. During the cladding process, the laser head is ensured to be perpendicular to the plane of the area to be clad, and the distance between the two is controlled at 10mm-15mm. The movement trajectory of the laser head during the cladding process is set according to the width of the weld, and the moving length of the laser head is 1.5 times the width of the weld to ensure that the cladding area covers the weld and the heat-affected zone of the weld. Since the alloy powder is not sensitive to the cladding process, when using a handheld laser cladding equipment, it is sufficient to control the cladding parameters within a certain range. The laser power during cladding is 800W, the moving speed of the laser head is controlled at 3cm / s-5cm / s, the stepping during the cladding process is 0.4mm-0.7mm, the powder feeding amount is 2kg / h, the powder feeding gas size is 5L / min, the flow rate of the shielding gas is 15L / min, and the average thickness of the protective coating for the welds of offshore wind turbines prepared is 680μm, and the surface iron content is controlled to be less than 5wt.%.

[0085] After applying a protective coating specifically for offshore wind turbine welds, the weld surface is polished using a wire brush and then an angle grinder to remove any cladding marks and maintain a smooth, clean weld surface. After the protective coating cools, the tower frame is coated with an anti-corrosion paint consisting of an epoxy zinc-rich primer, epoxy glass flake paint, and a polysiloxane topcoat.

[0086] Example 4

[0087] This embodiment provides a method for preparing a protective coating on the weld surface of an offshore wind turbine, which includes the following steps:

[0088] 1. Selection and preparation of corrosion-resistant alloy materials

[0089] The corrosion-resistant alloy material used is composed of 48 wt.% Cu, 2 wt.% Mo, 1 wt.% Si, 1 wt.% Al, 1 wt.% Sb, and the balance Ni. The powder has a mesh size of 200-400 mesh and is prepared using atomization powder production technology. The main steps include batching, smelting, atomization, and screening.

[0090] According to the composition of the alloy powder, corresponding masses of copper, nickel, aluminum, molybdenum, silicon and antimony are weighed as raw materials, ensuring that the surface of the raw materials is clean and free of pollution.

[0091] Before smelting, a vacuum pump was used to evacuate the atmosphere in the smelting chamber, and a nitrogen cylinder was used to provide protective nitrogen during the smelting process. The raw materials were weighed according to the specified mass fraction and placed in a water-cooled copper crucible in a vacuum medium-frequency induction heating furnace. The furnace was then evacuated to 50 Pa and filled with argon to 110 kPa. The smelting power was set to 200 kW, and the raw materials in the crucible were heated to 1400°C using a resistance wire to obtain a molten alloy. The holding power was then adjusted to 50 kW and the holding time was 10 minutes to ensure thorough mixing of the molten metal.

[0092] After the smelting process is completed, open the gas valve, fill the atomizing chamber with nitrogen, and turn on the water cooling device of the atomizing chamber. Open the atomizing gas valve, and the preheated high-purity, high-pressure nitrogen is accelerated through the Laval structure cavity to form a supersonic airflow. The gas velocity when it reaches the atomizing nozzle is 20m / s and the pressure is 4MPa. After the air velocity and pressure at the nozzle are stable, the molten metal obtained by smelting is slowly poured from the crucible into the tundish with a conduit. At this time, the melt temperature is 1350℃, and the flow rate of the molten metal is controlled to be 0.6kg / min.

[0093] The molten metal in the tundish is introduced into the nozzle and atomized into powder through the nozzle.

[0094] After atomization and pulverization, the powder is vibrated and sieved using 200-mesh and 400-mesh screens. After the powder is classified, the 200-400-mesh metal powder is quickly vacuum-packaged to prevent oxidation, thereby obtaining the corrosion-resistant alloy material.

[0095] 2. Thermal spraying of the weld area between the tower and the tower frame to prepare a protective coating for the welds of offshore wind turbines

[0096] The method used to carry out corrosion protection on the welds of the towers and towers of wind turbines that are already in operation is to use thermal spraying technology to prepare a protective coating for the welds of offshore wind turbines on the weld surface. Before preparation, use an angle grinder to grind off the rust and anti-corrosion paint on the weld surface, and grind off the anti-corrosion paint around the weld. The area to be sprayed is the weld, the welding heat-affected zone, and the surrounding part of the substrate. Use an angle grinder to grind the area to be sprayed smooth and neat. Then use anhydrous ethanol to spray the surface of the area to be sprayed to clean and remove the oil stains on the surface. For areas not to be sprayed, use asbestos to wrap them to prevent the thermal spraying process from affecting the non-sprayed area. The thermal spraying process can only be started after the sprayed area is dry and neat.

[0097] A handheld flame spraying device was used to prepare a protective coating for the welds of offshore wind turbines in the area to be clad. During spraying, the kerosene flow rate was controlled at 5 GPH, the oxygen flow rate was 1800 SCFH, the powder feed rate was 70 g / min, and the spraying distance was 300-400 mm. The average thickness of the sprayed coating was 683 μm. After preparation, the surface was smoothed using an angle grinder. After the coating cooled, anti-corrosion paint was applied to the sprayed area and surrounding areas. The anti-corrosion paint was epoxy zinc-rich primer + epoxy glass flake paint + polysiloxane topcoat.

[0098] Comparative Example 1

[0099] This comparative example provides a copper-nickel alloy cladding layer, wherein:

[0100] The copper-nickel alloy powder material consists of 25 wt% Cu and the balance Ni. The alloy powder was prepared using atomization. The parameters for the atomization process were: 180 kW melting power, 1200°C heating temperature, 80 kW holding power, 20 minutes holding time, and 6 MPa atomization pressure.

[0101] A copper-nickel alloy cladding layer was prepared on Q345B steel using a fiber laser. The laser power was 1700 W, the scanning speed was 9 cm / s, the step was 0.5 mm, the powder feeding rate was 3.5 kg / h, the powder feeding gas size was 4 L / min, and the shielding gas size was 15 L / min. The average thickness of the prepared copper-nickel alloy cladding layer was 604 μm.

[0102] Comparative Example 2

[0103] This comparative example provides a copper-nickel alloy cladding layer, wherein:

[0104] The copper-nickel alloy powder material consists of 45 wt% Cu and the balance Ni. The alloy powder was prepared using atomization. The parameters for the atomization process were: 200 kW melting power, 1400°C heating temperature, 80 kW holding power, 20 minutes holding time, and 6 MPa atomization pressure.

[0105] A copper-nickel alloy cladding layer was prepared on Q345B steel using a fiber laser. The laser power was 1800 W, the scanning speed was 10 cm / s, the step was 0.5 mm, the powder feeding rate was 3 kg / h, the powder feeding gas size was 4 L / min, and the shielding gas size was 18 L / min. The average thickness of the prepared copper-nickel alloy cladding layer was 620 μm.

[0106] Comparative Example 3

[0107] This comparative example provides a copper-nickel-molybdenum alloy cladding layer, wherein:

[0108] The copper-nickel-molybdenum alloy powder material consists of 45% Cu by weight, 2% Mo by weight, and the balance Ni. The alloy powder was prepared using atomization. The parameters for the atomization process were: 220 kW melting power, 1500°C heating temperature, 78 kW holding power, 20 minutes holding time, and 6 MPa atomization pressure.

[0109] A copper-nickel-molybdenum alloy cladding layer was prepared on Q345B steel using a fiber laser. The laser power was 1600W, the scanning speed was 7cm / s, the step was 0.5mm, the powder feeding rate was 3kg / h, the powder feeding gas size was 3L / min, and the shielding gas size was 13L / min. The average thickness of the prepared copper-nickel-molybdenum alloy cladding layer was 619μm.

[0110] Comparative Example 4

[0111] This comparative example provides a copper-nickel-molybdenum-aluminum alloy cladding layer, wherein:

[0112] The copper-nickel-molybdenum-aluminum alloy powder material consists of 45 wt% Cu, 2 wt% Mo, 1 wt% Al, and the balance Ni. The alloy powder was prepared using atomization. The parameters for the atomization process were: 210 kW melting power, 1400°C heating temperature, 80 kW holding power, 20 minutes holding time, and 8 MPa atomization pressure.

[0113] A copper-nickel-molybdenum-aluminum alloy cladding layer was prepared on Q345B steel using a fiber laser. The laser power was 1400 W, the scanning speed was 5 cm / s, the step was 0.5 mm, the powder feeding rate was 3 kg / h, the powder feeding gas size was 4 L / min, and the shielding gas size was 18 L / min. The average thickness of the prepared copper-nickel-molybdenum-aluminum alloy cladding layer was 610 μm.

[0114] Comparative Example 5

[0115] This comparative example provides a copper-nickel-molybdenum-aluminum-silicon-antimony-1 cladding layer, wherein:

[0116] The alloy powder material composition is Cu: 48wt%, Mo: 2wt.%, Al: 5wt.%, Si: 1wt.%, Sb: 1wt.%, and Ni: the balance. The alloy powder was prepared using atomization. The parameters for the copper-nickel-molybdenum-aluminum alloy powder atomization are: melting power 220kW, heating temperature 1300°C, holding power 70kW, holding time 20 minutes, and atomization pressure 8MPa.

[0117] A copper-nickel-molybdenum-aluminum alloy cladding layer was prepared on Q345B steel using a fiber laser. The laser power was 1300 W, the scanning speed was 6 cm / s, the step was 0.6 mm, the powder feeding rate was 3 kg / h, the powder feeding gas size was 4 L / min, and the shielding gas size was 14 L / min. The average thickness of the prepared copper-nickel-molybdenum-aluminum alloy cladding layer was 630 μm.

[0118] Comparative Example 6

[0119] This comparative example provides a copper-nickel-molybdenum-aluminum-silicon-antimony-2 cladding layer, wherein:

[0120] The alloy powder material composition is Cu: 48wt%, Mo: 2wt.%, Al: 1wt.%, Si: 3wt.%, Sb: 1wt.%, and Ni: the balance. The alloy powder was prepared using atomization. The parameters for the copper-nickel-molybdenum-aluminum alloy powder atomization are: melting power 200kW, heating temperature 1330°C, holding power 74kW, holding time 20 minutes, and atomization pressure 8MPa.

[0121] A copper-nickel-molybdenum-aluminum alloy cladding layer was prepared on Q345B steel using a fiber laser. The laser power was 1500W, the scanning speed was 7cm / s, the step was 0.5mm, the powder feeding rate was 3kg / h, the powder feeding gas size was 4L / min, and the shielding gas size was 14L / min. The average thickness of the prepared copper-nickel-molybdenum-aluminum alloy cladding layer was 610μm.

[0122] The alloy cladding layer prepared in the comparative example and the protective coating for the weld of an offshore wind turbine prepared in Example 1 were subjected to surface iron content testing, electrochemical testing, and hardness testing, respectively. The results are shown in Table 1. The cladding layers of Comparative Examples 5 and 6 had no passivation range in the electrochemical test results due to surface cracks.

[0123] The test method is as follows:

[0124] The elemental composition of the antifouling layer was measured using a handheld fluorescence analyzer (XL2-100G) to determine the Fe content on the coating surface. Before testing, the sample surface was polished flat and cleaned with alcohol. The surface was then examined using a spectrometer for 10 seconds.

[0125] Tafel plots of the samples in 3.5 wt.% NaCl solution were measured using a CHI660E electrochemical workstation. The passivation potential and passivation current density of the samples were obtained from the Tafel plots. The sample surfaces were ground and polished before testing, and the open circuit potential was measured for 1 hour to stabilize the sample surface.

[0126] The surface hardness of the sample was tested using an FM-300 microhardness tester with a load of 200 g and a holding time of 15 s. The same position was measured three times to obtain the average value.

[0127] Table 1

[0128]

[0129] As can be seen from Table 1, the corrosion resistance and hardness of the protective coating for the welds of offshore wind turbines of the present invention are better than those of the comparative example, and it can take into account both good mechanical properties and corrosion resistance.

[0130] Figure 2 The cross-sectional scanning electron microscope image of the protective coating for the weld of an offshore wind turbine in Example 1 and the element distribution curve of the cross-sectional view of the protective coating for the weld of an offshore wind turbine in Example 1 are shown. The left figure shows the cross-sectional scanning electron microscope image of the protective coating for the weld of an offshore wind turbine in Example 1, and the right figure shows the element distribution curve of the cross-sectional view of the protective coating for the weld of an offshore wind turbine in Example 1. Figure 2 As can be seen from the left picture, the protective coating of the weld of the offshore wind turbine is metallurgically bonded to the substrate, and there are no obvious cracks or holes at the interface. Figure 2 As can be seen from the right figure, the Fe element rapidly decreases to below 5wt.% within 50 microns from the substrate, and the surface Fe content is below 1wt.%.

[0131] Figure 3 Figure 2 shows the microscopic morphology of the protective coating for the weld of an offshore wind turbine in Example 1 after corrosion. The protective coating for the weld of an offshore wind turbine consists of a eutectic Mo-rich region 5 and a primary phase region 6. The higher Mo content in the eutectic can improve the protective coating's ability to resist intergranular corrosion in the weld of an offshore wind turbine.

[0132] Figure 4 The polarization curves of Q345B steel and the protective coating for the weld of offshore wind turbines in Example 1 in 3.5wt.% sodium chloride solution are shown. Figure 4 As can be seen, the corrosion potential of the protective coating for offshore wind turbine welds is -0.31 V, while the corrosion potential of Q345B steel is -0.67 V. The polarization curve of the protective coating for offshore wind turbine welds exhibits a stable passivation range, which is caused by the protective oxide film formed on the surface. Therefore, it can be seen that the protective coating for offshore wind turbine welds of the present invention has superior corrosion resistance compared to the Q345B steel substrate.

[0133] Figure 5Images show the effects of applying a protective coating to the weld surface of an offshore wind turbine. The left image shows the weld surface after welding, the middle image shows the weld and surrounding surfaces after polishing, and the right image shows the weld surface after applying a protective coating to the weld surface of an offshore wind turbine.

Claims

1. A corrosion-resistant alloy material, characterized in that: The corrosion-resistant alloy material comprises the following components by mass: Cu: 35-50%, Mo: 1-5%, Si: 0.8-1.5%, Al: 1-2%, Sb: 1-2%, and the balance is Ni.

2. The corrosion-resistant alloy material according to claim 1, characterized in that: The corrosion-resistant alloy material is in powder form with a particle size of 200 to 400 meshes.

3. The corrosion-resistant alloy material according to claim 1, characterized in that: The corrosion-resistant alloy material comprises the following components by mass: Cu: 45-50%, Mo: 1-3%, Si: 0.8-1.0%, Al: 1-1.5%, Sb: 1-1.5%, and the balance is Ni.

4. A method for preparing the corrosion-resistant alloy material according to any one of claims 1 to 3, characterized in that: include: Step S1, weighing raw materials of Cu, Mo, Si, Al, Sb, and Ni, placing them in a smelting container, evacuating to 1-100 Pa, then filling with a protective atmosphere to 105-110 kPa, and heating to 1300-1500° C. to obtain a molten alloy; Step S2, injecting the alloy liquid into an atomizing device for atomizing and powdering treatment, the atomizing temperature is 1160-1250° C., and the atomizing pressure is 3-4 MPa.

5. The preparation method according to claim 4, characterized in that: The step S2 comprises: The alloy liquid is introduced into an atomizing device with a nozzle, and a protective gas is introduced through the nozzle to perform atomization and powder making treatment; the flow rate of the protective gas when reaching the nozzle is 15-25 m / s, and the pressure is 3.5-4.5 MPa; the flow rate of the alloy liquid in the atomizing device is 0.2-0.8 kg / min.

6. The preparation method according to claim 4, characterized in that: After step S2, the preparation method further comprises: Step S3, screening the powder obtained by the atomization powder making process.

7. A protective coating for welds of offshore wind turbines, characterized in that: The invention is prepared from the corrosion-resistant alloy material according to any one of claims 1 to 3.

8. The protective coating for welds of offshore wind turbines according to claim 7, characterized in that: The protective coating for the weld of the offshore wind turbine has a thickness of 400 to 700 microns and a surface Fe content of less than 5 wt%.

9. A method for preparing a protective coating for a weld of an offshore wind turbine according to claim 7 or 8, characterized in that: include: The protective coating for the weld of the offshore wind turbine generator set is prepared on the weld surface by laser cladding technology, wherein the power of the laser is 1000-2000W, the beam diameter is 1-2.5mm, and the powder feeding method is annular synchronous powder feeding.

10. A method for preparing a protective coating for a weld of an offshore wind turbine according to claim 7 or 8, characterized in that: include: The protective coating for the weld of the offshore wind turbine is prepared on the weld surface by thermal spraying technology, wherein the powder feeding amount is controlled to be 60-80 g / min during spraying, and the spraying distance is 300-400 mm.